Sino-Christian Theology A Theological Qua Cultural Movement in Contemporary China - Lai, Pan-chiu; Lam, Jason (Studies in the Intercultural History of Christianity, 2010)
"Sino-Christian theology" usually refers to an intellectual movement emerged in Mainland China since the late 1980s. The present volume aims to provide a self-explaining sketch of the historical development of this theological as well as cultural movement. In addition to the analyses on the theoretical issues involved and the articulations of the prospect, concrete examples are also offered to illustrate the characteristics of the movement.